Transformation of a submerged flat jet under strong transverse magnetic field. (8th July 2021) - Krasnov, D.; Listratov, Ya.; Kolesnikov, Yu.; Belyaev, I.; Pyatnitskaya, N.; Sviridov, E.; Zikanov, O.
Abstract: A duct flow generated by a planar jet at the inlet and affected by a magnetic field perpendicular to the jet's plane is analyzed in high-resolution numerical simulations. The case of very high Reynolds and Hartmann numbers is considered. It is found that the flow structure is drastically modified in the inlet area. It becomes determined by three new planar jets oriented along the magnetic field lines: two near the walls and one in the middle of the duct. The downstream evolution of the flow includes the Kelvin-Helmholtz instability of the jets and slow decay of the resulting quasi-two-dimensional turbulence.